Innovation at the World Bank: Selective perspectives over three decades 1975 - 2005 - Roger Grawe (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
The World Bank is uniquely positioned to identify and disseminate innovative development practices. Based on his thirty-year experience as a World Bank staff member, the author takes an institutional perspective on the innovation climate at the World Bank focusing on dominant development paradigms, client and stakeholder relationships and the organization's operational toolkit as key factors influencing the climate for innovation. The interaction and impact of these factors are illustrated through selective examples of innovative programmes or practices.
Keywords: C21; F35; O1; O4; 330; innovation; institutions; development; projects